Ice thickness distribution of all Swiss glaciers based on extended ground-penetrating radar data and glaciological modeling. Issue 266 (20th December 2021) - Grab, Melchior; Mattea, Enrico; Bauder, Andreas; Huss, Matthias; Rabenstein, Lasse; Hodel, Elias; Linsbauer, Andreas; Langhammer, Lisbeth; Schmid, Lino; Church, Gregory; Hellmann, Sebastian; Délèze, Kevin; et al.
Abstract: Accurate knowledge of the ice thickness distribution and glacier bed topography is essential for predicting dynamic glacier changes and the future developments of downstream hydrology, which are impacting the energy sector, tourism industry and natural hazard management. Using AIR-ETH, a new helicopter-borne ground-penetrating radar (GPR) platform, we measured the ice thickness of all large and most medium-sized glaciers in the Swiss Alps during the years 2016–20. Most of these had either never or only partially been surveyed before. With this new dataset, 251 glaciers – making up 81% of the glacierized area – are now covered by GPR surveys. For obtaining a comprehensive estimate of the overall glacier ice volume, ice thickness distribution and glacier bed topography, we combined this large amount of data with two independent modeling algorithms. This resulted in new maps of the glacier bed topography with unprecedented accuracy. The total glacier volume in the Swiss Alps was determined to be 58.7 ± 2.5 km 3 in the year 2016. By projecting these results based on mass-balance data, we estimated a total ice volume of 52.9 ± 2.7 km 3 for the year 2020. Data and modeling results are accessible in the form of the SwissGlacierThickness-R2020 data package.